A Simple Method for Cost Estimating and Controlling - Fanny Fanny (IJNMT (International Journal of New Media Technology), 2018)
Based on software project survey from Standish Group’s “CHAOS Report”, 29% of software projects in large enterprises can be delivered on time and not over budget, 53% of software project were over budget or had some problem with the schedule, and 18% of software project were failed. This means that cost management is very important to prevent the possibility of project’s failure. Therefore, in this paper, we provide and recommend some methods and technique in order to do cost estimation and cost controlling as the crucial part of project cost management. We recommend Activity-Base Costing method for cost estimation and Earned Value Analysis for cost controlling. As the result of this paper, these two methods can be applied properly to real project and ease the project manager to estimate and control the cost of the project.